“From phenomenon, throughout the fact, to foundation”. Outline of the concept of man and its development according to Edith Stein (1891–1942) - Chrost, Sławomir (Biuletyn Historii Wychowania, 2019)
Edyta Stein – Sister Teresa Benedicta of the Cross – was fascinated by the “mystery of man”. Discovering this mystery led her to experience the “mystery of God”. She had a beautiful and difficult road leading through life and scientific transgressions, the path from thanatology to transthanatology, from the existence of a contingent existence to the existence of eternal Being. According to Edith Stein, the existence of man is unique. Everyone has to discover the fullness of his existence. Here comes Stein’s transition from psychological and philosophical considerations (phenomenon-fact) to theological considerations (foundation). By learning about God, man recognizes himself and discovers the ultimate truth of his existence. Whoever does not reach himself will not find God and enter eternal life. Or better: whoever does not find God will not find himself (no matter how much focus he will give on finding himself) and the source of eternal life that awaits him in his own interior.